The position of the reformist press (southern Algeria) on the French educational policy in Algeria Oudi Mizab newspaper by Sheikh Abu Al-Yakdan as a model (1926/1929) - Barka, mohamed; karimi, Khadija (The Algerian Historical Journal, 2026)
Perhaps various studies confirmed that the cultural and educational reality in the late Ottoman era was in line with the components of Algerian society, so the French colonizer used a new educational policy to strike the Algerian personality. He revitalized and revived the French language to run the administration under the civil system of government starting in 1870. To stabilize this, he took advantage of many means that link him to Algerian society, the most important of which is the press. At the beginning of the twentieth century, a reform movement emerged in Algeria led by national scholars and figures .Among them is Sheikh Abou El Yakdan, who was able to establish a national press with Algerian pens; Among the newspapers that we will highlight through their positions on French educational policy is the Ouadi Mizab newspaper. The purpose of the study is to shed light on the manifestations of the French educational policy in Algeria and to highlight the positions and opinions of the reformist press on this policy, especially at the beginning of the twentieth century, which witnessed the development of journalistic activity in Algeria.